2012
DOI: 10.1002/dc.22829
|View full text |Cite
|
Sign up to set email alerts
|

Focused rescreening of NILM Pap slides from women ≥30 years of age with positive high risk HPV DNA: An enhanced quality control measure

Abstract: CLIA 88 regulations specify that at least 10% of negative for intraepithelial lesion or malignancy (NILM) Paps be rescreened as a means of quality control (QC). With the incorporation of HPV DNA testing into American Society for Colposcopy and Cervical Pathology guidelines for women ≥ 30 years of age, a population of NILM patients with positive HPV results exists. Slides from this cohort were rescreened to judge the value of focused QC. Three hundred and eighty-six consecutive, NILM, HCII+, Paps (SurePath and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
6
1
Order By: Relevance
“…Interestingly, in both cases, a subset of cytotechnologists identified the rare HSIL cells in both phases of the study when the HPV status was provided and withheld. This suggests that a second review may have resulted in increased sensitivity in these cases, and this would support other literature that has recommended performing quality‐control reviews on all HPV‐positive NILM cases before sign‐out . However, even with knowledge of an HPV‐positive status, occasional HSIL cases may be missed; there were 3 instances in this study in which a cytotechnologist interpreted an HSIL case with a known HPV‐positive status as NILM (see Tables and ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, in both cases, a subset of cytotechnologists identified the rare HSIL cells in both phases of the study when the HPV status was provided and withheld. This suggests that a second review may have resulted in increased sensitivity in these cases, and this would support other literature that has recommended performing quality‐control reviews on all HPV‐positive NILM cases before sign‐out . However, even with knowledge of an HPV‐positive status, occasional HSIL cases may be missed; there were 3 instances in this study in which a cytotechnologist interpreted an HSIL case with a known HPV‐positive status as NILM (see Tables and ).…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that a second review may have resulted in increased sensitivity in these cases, and this would support other literature that has recommended performing quality-control reviews on all HPV-positive NILM cases before sign-out. 11,12 However, even with knowledge of an HPV-positive status, occasional HSIL cases may be missed; there were 3 instances in this study in which a cytotechnologist interpreted an HSIL case with a known HPV-positive status as NILM (see Tables 2 and 3). At the time of this study, our institution did not use the HPV status for sending cases to quality assurance.…”
Section: Discussionmentioning
confidence: 81%
“…Our results along with those of previous studies raise questions regarding the effectiveness of mandatory routine 10% rescreening. In an effort to reduce the false‐negative rate of the Pep test, several investigators have proposed focused rescreening . In a study performed by Sturgis et al, 386 NILM Pap tests with positive hrHPV results were rescreened and 50 (13%) were upgraded to ASC‐US or higher, which resulted in detecting ten times more SIL lesions than routine 10% Pap slide review.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few attempts to identify novel cytomorphologic features that can predict HPV infection in samples that were initially diagnosed with NILM or ASCUS based on the diagnostic criteria presented by the Bethesda system . Bollmann et al tested a PCR‐based HPV assay that could detect 16 HPV genotypes and suggested a predictive model combined with 4 cytomorphologic alterations (namely, subtle nuclear changes, disordered keratinization, abortive koilocytes and measles cells, and degenerative changes), which are mainly focused on high‐power fields observed using the ThinPrep‐based preparation.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] There have been a few attempts to identify novel cytomorphologic features that can predict HPV infection in samples that were initially diagnosed with NILM or ASCUS based on the diagnostic criteria presented by the Bethesda system. 6,[22][23][24] Bollmann et al 6 4 Accordingly, false-negative results for these 2 HPV types may lead to critical outcomes in patients.…”
Section: Discussionmentioning
confidence: 99%